Traumatized refugees: identifying needs and facing challenges for mental health care - Christine Knaevelsrud; Nadine Stammel; Miranda Olff (European Journal of Psychotraumatology, 2017)
In the past few years the number of refugees worldwide has increased dramatically. Many of them were traumatized in their homelands due to violent conflict or persecution, as well as during their flight, and are confronted with ongoing stressors in the exile countries. In order to contribute to enhancing the clinical knowledge, this special issue of the European Journal of Psychotraumatology focuses on traumatized refugees. It includes three review articles as well as four original articles on the mental health burden, screening instruments and interventions in different groups of refugees. The articles published in this special issue focus on important aspects of better understanding the needs of traumatized refugees, as well as on identifying and offering appropriate mental health care for this population. Future research recommendations are provided in the hope to contribute to improving mental health care strategies of this still underserved population.